2021
DOI: 10.1016/j.advwatres.2020.103759
|View full text |Cite
|
Sign up to set email alerts
|

Verification benchmarks for single-phase flow in three-dimensional fractured porous media

Abstract: Flow in fractured porous media occurs in the earth's subsurface, in biological tissues, and in man-made materials. Fractures have a dominating influence on flow processes, and the last decade has seen an extensive development of models and numerical methods that explicitly account for their presence. To support these developments, four benchmark cases for single-phase flow in three-dimensional fractured porous media are presented. The cases are specifically designed to test the methods' capabilities in handlin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
97
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(112 citation statements)
references
References 29 publications
6
97
0
Order By: Relevance
“…This last example considers the simulations of a 3D problem taken from another benchmark study [6], a threedimensional analogue to the test case in Section 5.1. The geometry is extended to the unit cube and the fracture network now consists of 9 fracture planes, 69 intersection lines and 27 intersection points (see Fig.…”
Section: Example: Three-dimensional Regular Fracture Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…This last example considers the simulations of a 3D problem taken from another benchmark study [6], a threedimensional analogue to the test case in Section 5.1. The geometry is extended to the unit cube and the fracture network now consists of 9 fracture planes, 69 intersection lines and 27 intersection points (see Fig.…”
Section: Example: Three-dimensional Regular Fracture Networkmentioning
confidence: 99%
“…These methods mostly differ in two aspects: whether the fractures conform to the discrete grid of the porous medium [9] or are placed arbitrarily within the grid [13,17,32], or whether pressure or flux continuity is preserved. Comparison studies of different discretization methods and their properties can be found in [6,16,29].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, hybriddimensional models rely on the assumption of negligible aperture. However, fracture apertures which are two-orders-of-magnitude less than the background size are often encountered [10,5,2]. In these cases, the assumption of negligible aperture is not applicable and the error coming from the lower-dimensional representation of the fractures may dominate the discretization error.…”
Section: Introductionmentioning
confidence: 99%
“…benchmark case 1 fromBerre et al (2020), who compare 17 different methods of simulating single-phase flow in fractured porous media. The initial setup (displayed in a) in figure A2) consists of an inclined fracture with an hydraulic aperture of 10 −2 m embedded in a cube of 100 m length with a matrix hydraulic conductivity of 10 −6 m 2 , whereas the hydraulic conductivity of a small band of 10 m width at the bottom is increased to 10 −5 m 2 .…”
mentioning
confidence: 99%
“…CC BY 4.0 License. Benchmark case fromBerre et al (2020). a) shows the benchmark geometry of an embedded fracture (aperture of 10 −2 m)…”
mentioning
confidence: 99%